Functionalization of wool fabric with phase‐change materials microcapsules after plasma surface modification. Issue 5 (23rd August 2012) - Oliveira, Fernando Ribeiro; Fernandes, Marta; Carneiro, Noémia; Pedro Souto, António
Abstract The use of microcapsules has increased in several different areas, namely, textile applications. They have been used as a possible means of introducing new properties, namely, in medical care by antibiotics, skin moisturizers, and other drugs and for thermal comfort. In this study, we examined the influence of dielectric barrier discharge (DBD) plasma treatment on the adhesion of phase‐change material (PCM) microcapsules on wool fabric. Several experimental techniques were used to evaluate the wool surface modification after plasma treatment and the influence of the microcapsules' resistance to washing conditions, namely, the determination of the static and dynamic contact angles, surface energy, and adhesion work; X‐ray photoelectron spectroscopy; Fourier transform infrared spectroscopy; differential scanning calorimetry; and scanning electron microscopy. Chemical and physical characterization of the wool fiber in the fabric confirmed significant surface modification. The plasma treatment greatly increased the hydrophilicity, surface energy, and adhesion work of the wool fabric; this proved that more microcapsules were adsorbed on the fabric and more microcapsules remained on the fabric surface after the washing procedures. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013